Green Plot Ratio and MUtopia: The integration of green infrastructure into an ecological model for cities - Ong, Boon; Fryd, O.; Hes, D.; Ngo, T. (earthscan from Routledge, 2017)
As urban population continues to grow in terms of both number and percentage of people on the planet, the role of urban greenery will grow in terms of significance. Unfortunately, the value of urban greenery is currently contested – on the one hand, the environmental and ecological value of greenery is well established, but on the other hand, urban greenery is a man-made construction that consumes much energy and resources and, not uncommonly, further contributes to pollution through the use of pesticides. A significant value of ecosystem services through greenery is that its presence promotes an aesthetic response as part of our overall attraction to nature, or biophilia. This chapter discusses the application of the Green Plot Ratio (GPR) into a Precinct Information Management (PIM) tool to investigate the effects of urban greenery in cities. The GPR is a tool that can be used to quantify the extent of urban greenery in a given project. The current project applies GPR to an existing PIM application – MUtopia – to enable an investigation into how one might consider greenery as part of densification strategies. Sustainable infrastructure and green infrastructure are seen to serve different purposes: the first relates to energy, water supply and waste management while the second deals with matters of health, biodiversity and air quality. Ideally, and in certain contexts, the two may overlap. We propose a model in which both agendas can be integrated within a single model. The integration of greenery into an evaluative tool for urban design has the added value of promoting design and aesthetics as an expression of human ecological behaviour.